Prognostic Factors Influencing the Outcome of 64 Consecutive Patients Undergoing Surgery for Metastatic Melanoma of the Spine. Issue 3 (30th April 2015) - Sellin, Jonathan N.; Gressot, Loyola V.; Suki, Dima; St. Clair, Eric G.; Chern, Joshua; Rhines, Laurence D.; McCutcheon, Ian E.; Rao, Ganesh; Tatsui, Claudio E.
Abstract: BACKGROUND: Melanoma metastases to the spine remain a challenge for neurosurgeons. OBJECTIVE: To identify factors associated with survival in a series of patients who underwent spinal surgery for metastatic melanoma. METHODS: We retrospectively reviewed all patients (n = 64) who received surgical intervention for melanoma metastases to the spine at the University of Texas MD Anderson Cancer Center between July 1993 and March 2012. RESULTS: No patients were excluded from the study, and vital status data were available for all patients. Median overall survival was 5.7 months (95% confidence interval, 2.7-28.7). On univariate survival analysis, diagnosis of spinal metastasis after prior diagnosis of systemic metastasis, higher total spinal disease burden (including but not exclusive to the operative site), presence of progressive systemic disease at the moment of spine surgery, and postoperative complications were associated with poorer overall survival, whereas the presence of only bone metastasis at the moment of surgery was associated with improved overall survival. On multivariate survival analysis, both progressive systemic disease at the moment of spine surgery and total spinal disease burden of ≥3 vertebral levels were significantly associated with worse overall survival (hazard ratio, 6.00; 95% confidence interval, 3.19-11.28; P .001; and hazard ratio, 2.87; 95% confidence interval, 1.62-5.07; P .001, respectively). CONCLUSION: On multivariate analysis, involvement of ≥3 vertebral bodies and progressive systemic disease were associated with worse overall survival. Consideration of these factors should influence surgical decision making in this patient population.